Profil Klinikopatologi Meningioma di Instalasi Patologi Anatomi RSUD Dr. Saiful Anwar Malang Periode Tahun 2016-2020 - Putri, Anggie Sasmita Kharisma; Retnani, Diah Prabawati; Dewi, Rose Khasana; Angelina, Aina; Diah Prabawati (RSUD Dr. Saiful Anwar Province of East Java, 2023)
Background. The most common intracranial neoplasms worldwide is meningioma. It has been classified into three grades by World Health Organization (WHO) in which each grade has several histological variants. The prognosis of meningioma is affected by many factors including histopathological type of tumor, age, and gender. Objective. The aim of this study is to determine the frequency of meningioma based on histopathological type, age, and gender from 2016 to 2020 in Saiful Anwar General Hospital Malang. Methods. This study was a quantitative descriptive study and data was collected from medical records from 2016 to 2020 in Department of Anatomic Pathology, Medical Faculty, Brawijaya University, Saiful Anwar General Hospital Malang. Histopathological type of meningioma, age, and gender were acquired. Results and Discussion. From 2016 to 2020, there were 96 eligible cases of meningioma. Ratio of men to women was 1:12.7. Meningioma was most commonly found in age group 4150 years old (43.75%). The most common histopathological type of meningioma was meningotheliomatous meningioma (37.5%). The average of meningioma cases was 19 per year. In this study, there was an increase in incidence rate of meningioma in 2017, and decreased in 2020. It may happen because The government has a better referral system to provide health care, thus meningioma can be detected earlier. Conclusion. Frequency of meningioma is higher in women than men, and increases with age until 50 years, which then decreases. Meningotheliomatous meningioma is the most common histopathological type in this study.